Forced relocations of the Kola Sámi people: background and consequences - Afanasyeva, Anna (Universitetet i Tromsø, 2013)
This Master’s thesis describes and analyses the background and consequences of the relocation policies imposed on the Kola Sámi people. The forced relocations of the Kola Sámis in this work are presented in a two-staged process implying that the main policies, leading to gradual spatial rearrangement of the Sámi traditional settlement patterns and its further displacement. Another purpose of this work is to discuss the ways in which the Kola Sámi community was affected by the forced relocations. The decades of relocations represent a turning point in history of the Sámi community as associated with the new society-building patterns, restructuring traditional economies and need for active cultural and language preservation today. The Kola Sámi community faced the loss of their resource territories, disruption of traditional activities’ practice along with strong influences of multicultural environment on language and culture as the impacts of forced relocation policies. The change in geographical distribution of the Sámi settlements has also caused shifts in communities’ social organization and land use patterns. The current work addresses implementation of the Soviet policies of forced relocations on the Kola Sámi people and touches upon the occurred consequences.